The Role of HLA-B27 in Argentinian Axial Spondyloarthritis Patients. Issue 2 (17th March 2022) - García-Salinas, Rodrigo; Ruta, Santiago; Chichande, Jessica Torres; Magri, Sebastian
Abstract : Background: The prevalence of human leukocyte antigen B27 (HLA-B27) is variable around the world. Our objectives were to estimate the frequency of HLA-B27 in an Argentinian cohort of axial spondyloarthritis (axSpA), to evaluate the differences between HLA-B27–positive and HLA-B27–negative patients, and to analyze its performance as a diagnostic biomarker. Methods: Observational study including patients older than 18 years, with axSpA diagnosis assessed in a fast track program (Reuma-Check SpA). All patients underwent the following: blood tests, HLA-B27, sacroiliac images, and enthesitis ultrasound. Sociodemographic data and SpA symptoms were also collected. The clinical assessor was blinded to complementary studies. For the sensitivity and specificity analysis, patients with chronic low back pain without axSpA who performed the same circuit in the same period were used as control, paired 1:1 (sex and age). Results: One hundred fifty patients were included, 75 axSpA and 75 controls. The frequency of HLA-B27 was 43% (95% confidence interval [CI], 30–53). The differences between HLA-B27–positive and HLA-B27–negative patients were observed in age of low back pain onset (36 vs 46 years), BASFI (Bath Ankylosing Spondylitis Functional Index) (4 vs 5), and extra-articular SpA features such as uveitis and inflammatory bowel disease (29% vs 50%). When this frequency was compared (low back pain control group), the difference was 43% versus 9% (odds ratio, 7.7; 95% CI, 2.8–24), and HLA-B27 had a sensitivity of 43%, specificity of 91%, positive predictive value of 85%, negative predictive value of 58%, and likelihood ratio of 4.9 (95% CI, 3–8). Conclusions: The frequency of HLA-B27 in axSpA was 43%; positive patients had an earlier age of onset (36), a higher BASFI, and more SpA features. For the diagnosis of SpA, HLA-B27 had a good specificity but low sensitivity.